CNC Parametric Optimization for Exercise Equipment Parts Surface Roughness Using TRIZ - Han-Chen Huang; Cheng-I Hou; Tian-Syung Lan (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Product quality is the most important issue in the Computer Numerical Control (CNC) process. Hence, with exercise equipment parts Surface Roughness as the target, this study selected Spindle speed, Cutting depth, Feeding, and Tool runoff, as control parameters in CNC parametric optimization of target quality. By using the Theory of Inventive Problem Solving (TRIZ) to define the Cause and Effect relationship and conflicting points, this study quickly identified an optimal solution, according to TRIZ, and determined factor relevance by cutting control parameters. By the 40 Inventive Principles of TRIZ corresponding to Contradiction Matrix, we obtained the Surface Roughness optimization strategy. The empirical research results suggest that Surface Roughness can actually be improved under the optimal parameter combination. The effectiveness and practicality of the proposed method are verified.